Reformulation of Islamic Law in Indonesia: Study on Indonesian Ulama Council’s Fatwa - Ansori, Ansori; Labib, Mughni; Marwadi, Marwadi (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2021)
One of the institutions where ulama perform ijtihad with Islamic legal thought products in the form of fatwas is the Indonesian Ulama Council (MUI). Of the many fatwas that have been issued by the MUI, there are a number of fatwas that are formulated such as the fatwa of the pilgrimage and umrah pilgrimage, the initial determination of Ramadan, Shawwal, Zulhijjah, qibla direction, abortion, donation of social funds with prizes (SDSB), and the use of meningitis vaccines for hajj and umrah pilgrims. MUI reformulates the fatwa due to socio-cultural changes in the community and advances in science and technology. MUI is very concerned about the condition of social, cultural and political changes in society and the progress of science and technology as a material consideration in formulating fatwa. Such a thing is very relevant to the process of renewing Islamic law in Indonesia which has been going on since the 70s until now.Â